Left. No. 76, What they say about the Beveridge Report ([London : Controversy Pub. Co.])
1943-01 1943 1940s 8 pages Percy Rockliff, secretary of the Joint Committee of Approved Societies and the National Union of Friendly Societies: — The author of this report is an economist turned spendthrift. Having himself exchanged frugality for thriftlessness, he has no further use for either friendly or approved societies. He would push compulsorily — not a section of the community — but the whole nation back into the days of a glorified Poor Law system, destroying in the process every vestige of self-reliance and self-help which during the past century or more has permeated and strengthened the British character. After 1944, if this scheme were to come to pass, truly might Ribbentrop allege that the Anglo-Saxon race was decadent. Throughout the existence of this Beveridge Committee, its chairman has been in close association with Left Wing politicians. Their antipathy to commercial life assurance has for many years been a feature of their party propaganda. Truth (4.12.42). — If the Plan is ever implemented ... it is quite evident that the land which will emerge will be the very nightmare of Paternalism or if the word is preferred Totalitarianism. A few responsibilities and freedoms will be left to the man and woman but very few. LABOUR SUPPORT Enthusiastic support came from the Labour Press: the Daily Herald, Reynolds, New Statesman, Labour Press Service and Labour Discussion Notes. New Statesman (5.12.42): "There is not the smallest doubt that the Beveridge Plan is worth backing through thick and thin. It would be easy to pick holes . . . but what fundamentally matters is that it lays the right foundations." Herbert Tracey in L.P.S. (9.12.42): "Whatever may be said about the incidence of the Beveridge proposals in relation to Trade Union practice and methods of work, the Plan as a whole clearly conforms to trade Union principles, objects and aims." L.D.N. (Dec., 1942): "Greater even than the importance of the actual proposals of the Beveridge Report is its importance as a test and touchstone of our political future as a democracy . . . Above all, it is a challenge to our Labour Movement. If we falter on this issue, the people at large will say, 'Labour is as bad as the rest. It can't get real things through.'" Daily Herald (2.12.42). — We welcome most heartily the publication of the Beveridge Report. Trade Unionism and the Labour Party feel a special satisfaction at its appearance. For it was the insistent pressure of the Trades Union Congress upon the Government Departments that made plain the need for such an investigation as Sir William has conducted. And it was a Labour leader — Mr. Greenwood, when as a member of the War Cabinet he had charge of planning for reconstruction — who invited Sir William to perform the task. Our pleasure and our gratitude to the author of the Report for his massive achievement does not of course mean that we endorse 9 172/BE/7